Characteristics of house dust mite allergens in Southeast and East Asia with the effect of hygienic practices - Donghyun Kim; Hyunwoo Jeon; Ji Young Park; Hidayatulfathi Othman; To Thi Hien; Puji Lestari; Kraichat Tantrakarnapa; Kiyoung Lee (Elsevier, 2024)
House dust mite allergens (HDMAs) are a major allergen that can cause severe adverse health effects, such as allergic rhinitis, asthma, and dermatitis. This study aimed to characterize the HDMA levels in bedding dust from Southeast and East Asian countries and evaluate the impact of hygiene practices on these levels. Bedding dust samples were collected from 29, 82, 32, 31, and 86 households in Indonesia, Malaysia, Thailand, Vietnam, and South Korea, respectively. Of the households in Malaysia and South Korea, 57 each had received mattress care services. The samples were analyzed for Dermatophagoides farinae type 1 (Der f1) and Dermatophagoides pteronyssinus type 1 (Der p1). The detection rates of Der f1 and Der p1 varied among the countries, especially in households that had not received mattress care services. In Indonesia, the detection rates of Der f1 and Der p1 were similar (97%). In Malaysia, Thailand, and Vietnam, the detection rates of Der f1 were higher than those of Der p1. South Korea exhibited the lowest detection rates for both Der f1 (76%) and Der p1 (7%). In Indonesia and Malaysia, the levels of Der p1 were higher than those of Der f1. In Thailand and Vietnam, the levels of Der f1 were higher than those of Der p1. In both Malaysia and South Korea, households that had received mattress care services exhibited lower HDMA levels than those that had not. Furthermore, households serviced within the past month had notably lower HDMA levels than those serviced more than two months prior. This study observed significant regional differences in the detection rates and levels of HDMAs among Southeast and East Asian nations. In addition, the study observed significant decrease in the levels of HDMAs following routine mattress care service, highlighting the pivotal role of consistent hygienic practices for diminishing potential allergenic hazards. However, the study could not identify specific regional factors affecting the type and level of HDMAs.